Modeling and Interpretation of Geothermal System Components Using the Gravity Method at the “X” Geothermal - Ibrahim, Mochammad Malik; Utami, Pri; Raharjo, Imam Baru (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
Geothermal field "X" is one of the geothermal fields located in North Sulawesi Province managed by PT Pertamina Geothermal Energy. This research aims to determine the presence of geothermal system components in the subsurface using the gravity method. Gravity method data processing is processed with observational and theoretical corrections to obtain a complete Bouguer anomaly. The complete Bouguer anomaly is separated into regional and residual anomaly using the upward continuation process. The results of modeling and interpretation of residual (shallow) gravity prove the existence of 3 (three) rock layers and their density values, Post Tondano Andesite Unit layer (2,4 g/cm3), Tondano Rhyolite Unit layer (2,5 g/cm3) and Pre Tondano Andesite Unit layer (2,7 g/cm3). The results of modeling and interpretation of regional (deep) gravity evidence the existence of 3 (three) rock layers along with the rock density value, Tondano Rhyolite Unit layer (2,5 g/cm3), Pre Tondano Andesite Unit layer (2,7 g/cm3) and diorite intrusion rock layer (2,9 g/cm3). The geothermal system in the research area is composed of Post Tondano Andesite Unit as overburden rock, Tondano Rhyolite Unit as caprock, Pre Tondano Andesite Unit as reservoir rock and Diorite intrusion rock as heat source.